Persepsi Petani terhadap Pilihan Menjual Padi Kepada Penebas atau Perpadi (Kasus Subak Benel, Desa Kaliakah, Kecamatan Negara, Kabupaten Jembrana) - I MADE PRASADA ARY WIRAWAN; I DEWA PUTU OKA SUARDI; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Farmers Perception Of Options To Sell Rice Penebas Or Perpadi(especially in Subak Benel, Kaliakah Village, Negara districts,Jembrana Regency) Various efforts have been implemented by the Provincial Food Crops Agency of Balito stabilize the price of grain, this is done by giving Funds of Rural EconomicEmpowerment Capital to the government for the purchase of rice. Although it hasbeen done from 2003, farmers are still selling it to Penebas with a bondage system.The purpose of this study to determine the perception of farmers to the choice ofselling rice to Perpadi or Penebas seen and differences in farmers' perceptions of thechoice of selling rice to Penebas or Perpadi. The research location is located in SubakBenel, Kaliakah Village, State District, Jembrana District. The analytical methodused is qualitative descriptive that aided with score, to answer the purpose ofresearch by using questionnaire. The results of this study indicate that the perceptionof farmers to the choice of selling rice to Perpadi better than to Penebas. This is seenin the achievement of the farmers' choice of selling paddy to Perpadi is very goodand to Penebas is good. The difference of Perpadi with Penebas is measured throughDifferent Test with SPSS Independent Sample T test program which the result of Sigvalue. Or p value of 0.004 where <0.05 then there is a statistically significantdifference in probability 0.05, the mean difference or mean of both groups is shownin Mean Difference ie .29559.